First report of johnsongrass mosaic virus in Argentina - Trucco, Veronica Milagros (2019)
Potyviruses are responsible for important economic losses in maize crop. This work reports the detection of johnsongrass mosaic virus, a potyvirus affecting maize in Argentina. Electron microscopy studies, mechanical transmission tests and molecular assays based on the CP gene were performed. To our knowledge, this is the first detection of JGMV in Argentina.